Managing Learning Excellence in Educational Institutions: Strategies and Insights - Karwanto Karwanto; Muhammad Faizal Bin Abdul Ghani; Windasari Windasari; Ima Widiyanah; Shelly Andari; Muhamad Sholeh; Syunu Trihantoyo (IJORER : International Journal of Recent Educational Research, 2025)
Objective: This study aims to identify and analyze the management of learning excellence in education units with different characteristics. Method: This research uses a qualitative approach with a multi-case study design. Data collection techniques used in-depth interviews, participant observation, and documentation studies. Data credibility was checked using triangulation techniques, member checking, and peer discussion. Data collected through the three techniques were organized, interpreted, and analyzed repeatedly through within-case and cross-case analyses to develop concepts and abstractions of research findings. Results: The results show that the existence of schools in superior schools is determined by the number of learning excellence owned by schools and the involvement of school principals in improving and maintaining progress by making innovations and changes so that schools remain stable and last until now. Future research can be conducted using different research designs and approaches. Novelty: Based on the results of the literature search, not many studies have been related to the management of learning excellence in education units. Previous research is mainly related to the characteristics of excellent schools. Only some studies aim to determine and analyze the management of learning excellence in schools. Therefore, the management of learning excellence has the characteristics of applying discipline in the teaching and learning process, demanding creative and innovative teachers, and having seriousness in curriculum development and learning.